Food based oral rehydration therapy: towards a better cholera treatment - Chandrika Murugaiah; Praneetha Palasuberniam; Mohamad Salih Falah; Hassanain Al-Talib (2015)
Prompt restoration of lost fluids and salts is the primary goal of cholera treatment. Oral rehydration therapy (ORT) with high-osmolarity mixture of glucose and salts has been recommended by the World Health Organization (WHO) and proved to be safe and effective in treating and preventing dehydration in cholera patient. The standard WHO-oral rehydration salt (WHO-ORS) prevents millions of deaths each year. Studies of food-based ORS versus WHO-ORS, demonstrated an improved outcome such as reduce purging, short duration of watery diarrhoeas, early recovery and low hospitalization rate. Moreover, food-based ORS provide additional nutrients to supplement WHOORS. In the short term, recommending food-based ORS will probably benefit a greater number of cholera patients.